2011
DOI: 10.1080/16506073.2011.616218
|View full text |Cite
|
Sign up to set email alerts
|

Attention Modification in Persons with Fibromyalgia: A Double Blind, Randomized Clinical Trial

Abstract: Contemporary models of chronic musculoskeletal pain emphasize the critical roles of fear, anxiety, and avoidance as well as biases in attention in the development and maintenance of chronic pain disability. Evidence supports the influence of individual difference variables such as anxiety sensitivity, pain-related anxiety, and catastrophizing on the pain experience and on pain-related attentional biases. Changes in attentional biases have been associated with treatment gains in patients with clinically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
44
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 70 publications
9
44
0
1
Order By: Relevance
“…Training early orienting, and not maintained attention, towards neutral words produced significant increases in pain threshold and tolerance, and there was a trend-level reduction in pain severity at 30 s, in comparison with an ABM-Placebo group. Current findings align with studies reporting therapeutic effects of ABM for persistent pain (Carleton et al, 2011;Sharpe et al, 2012Sharpe et al, , 2015Schoth et al, 2013), providing evidence that attentional retraining in early orienting affects fundamental pain processes. Importantly, both studies found a significant impact of ABM-500 on pain threshold, strengthening evidence that the faster bias influences time taken to first register pain.…”
Section: Discussionsupporting
confidence: 81%
“…Training early orienting, and not maintained attention, towards neutral words produced significant increases in pain threshold and tolerance, and there was a trend-level reduction in pain severity at 30 s, in comparison with an ABM-Placebo group. Current findings align with studies reporting therapeutic effects of ABM for persistent pain (Carleton et al, 2011;Sharpe et al, 2012Sharpe et al, , 2015Schoth et al, 2013), providing evidence that attentional retraining in early orienting affects fundamental pain processes. Importantly, both studies found a significant impact of ABM-500 on pain threshold, strengthening evidence that the faster bias influences time taken to first register pain.…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were found in a group of fibromyalgia patients, where ABM alone resulted in clinical benefits to patients in comparison to placebo (Carleton et al, 2011) and in a small case series (Schoth et al, 2013). In the chronic pain group, participants received either four sessions of ABM or placebo and then received a standard, eight-session cognitive behaviour therapy (CBT) programme.…”
Section: Introductionsupporting
confidence: 63%
“…Recent research has also shown that changes in attentional biases (i.e., a decrease in vigilance attentional bias) can decrease the symptomatology of anxiety disorder and self-reported pain (e.g., Carleton, Richter, & Asmundson, 2011). These results support the contention that attentional biases may be associated with problems in the development and maintenance of pain.…”
supporting
confidence: 57%